AUKUS and the Nuclear-Free Norm in Southeast Asia: A Constructivist Analysis of ASEAN Responses (2023-2025) - Dewi Puspa Maharani; Khoirunnisa Khoirunnisa (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This study discusses how ASEAN member states respond to the AUKUS nuclear-powered submarine program in relation to the Southeast Asia Nuclear-Weapon-Free Zone (SEANWFZ) during the 2023-2025 period. Rather than treating AUKUS only as a military technology transfer, this study analyses it as a contested social object whose meaning differs across ASEAN states. Using an interpretive qualitative approach through document analysis, the study evaluates ASEAN and AUKUS policy documents, IAEA reports, selected policy studies, and peer-reviewed journal articles for their relevance to each country’s official stance and foreign policy orientation. The findings show ASEAN responses fall into three analytical categories: Indonesia, Malaysia, Cambodia, and Myanmar are positioned as critical or rejector (with Myanmar treated as an inferred low-confidence case due to the absence of direct official statements). The Philippines, Singapore, and Vietnam are categorized as conditional acceptors (with Vietnam also treated as an inferred case rather than a definitive official position). Thailand, Brunei, Laos, and Timor-Leste represent cautious neutrality or strategic silence. This study argues that ASEAN responses are shaped not only by material power distribution but also by strategic identity, threat perception, alliance orientation, normative commitment to the SEANWFZ, and ASEAN centrality. Theoretically, the study contributes to constructivist analysis by showing how nuclear-powered submarines become meaningful through regional identity and intersubjective interpretation. It also contributes to the scholarship on norm contestation by showing that AUKUS does not necessarily challenge the validity of SEANWFZ. However, it does contest how the nuclear-free norm should be applied to nuclear-powered but conventionally armed submarines.